Reading affect in post-apartheid literature: Compassion and other difficult feelings in Ivan Vladislavić - Schultz, Clea (My University, 2014)
I aim to explore compassion and affect in South African literature because there is a remarkable dearth of criticism on both compassion and affect in this field. I hope this thesis will be a small remedying contribution. As I wish to explore material conceptions of compassion and affect, this study will also engage in commentary on everyday South African society as reflected by the “web cracked mirror” (Titlestad and Gaylard, 7) held up to it: its literature. My case study is Ivan Vladislavić because he is a writer intricately engaged with everyday South African society, particularly the material realities and lived experiences of the people living within it. He never uses the word “compassion” in his texts, excepting in the mouth of Merle in The Restless Supermarket. (192) Nevertheless, the way in which he chooses and portrays his subject matter is infused with compassion, albeit in his aloof style. I have come to this conclusion through close reading of three of his texts – The Restless Supermarket, The Exploded View and Portrait with Keys – and intend to make close reading a large part of this thesis. I must also state this thesis will be my own personal enquiry and research, not an empirical project. The nature of affect is such that a study of affect must always be deeply subjective and, in fact, affected.